2012
DOI: 10.1063/1.4752454
|View full text |Cite
|
Sign up to set email alerts
|

Electron backscatter diffraction on femtosecond laser sulfur hyperdoped silicon

Abstract: This paper analyzes the impact of femtosecond laser pulse irradiation on the crystallinity of silicon wafers by means of electron backscatter diffraction (EBSD) measurements. EBSD based image quality maps and orientation imaging microscopy maps are correlated to the grade of the silicon crystallinity. We analyze the impact of accumulated net laser irradiation originating from a laser spot overlap that is necessary to process macroscopic areas, e.g., for sulfur doping of semiconductor devices. Furthermore, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…The area probed is small compared to the laser spot size (460-lm diameter) to minimize the spatial variation of the local laser fluence across the SIMS sample region (<1%). We record counts of 29 Si, 32 S, 34 S, 19 F, and 18 O, and the S and F counts are calibrated against known ionimplanted Si samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The area probed is small compared to the laser spot size (460-lm diameter) to minimize the spatial variation of the local laser fluence across the SIMS sample region (<1%). We record counts of 29 Si, 32 S, 34 S, 19 F, and 18 O, and the S and F counts are calibrated against known ionimplanted Si samples.…”
Section: Methodsmentioning
confidence: 99%
“…Gimpel et al show that the amorphous phase is also enhanced when scanning the laser pulses, as is commonly done when fabricating large-area hyperdoped Si. 19 For large area fabrication, the amorphous region could be minimized using a flat-top beam.…”
Section: A Crystalline Phasementioning
confidence: 99%
“…Black Si surface textures consist of densely packed needle-like peaks and pits of irregular shape and high aspect ratios (see Figure 1.4(a)). Black silicon can be prepared by several methods such as metal-assisted wet-chemical etching, inductively coupled reactive ion etching (ICP-RIE), or short-pulse laser irradiation [11][12][13][14][15]. Another important advantage of b-Si over conventional pyramidal textures is the comparatively large feature sizes of the latter.…”
Section: Scattering Structures For Optical Path Enhancementmentioning
confidence: 99%
“…On the other hand, annealing processes are investigated in correlation with structural changes in the silicon lattice. 12,13 It is found that annealing at T ¼ 800 C improves the crystal quality. 12,13 However, it remains still unclear if the impact of annealing influences the pn-junction.…”
mentioning
confidence: 98%
“…3,10 The chalcogens are impurities incorporated far above the solubility limit. 11,12 The required incorporation techniques diminish the silicon crystal quality, 11,13 leading to intrinsic defects in the silicon lattice. Subsequent thermal processes enhance among others the performance of a pn-junction with such a sulfur emitter.…”
mentioning
confidence: 99%